CSDP-NATO: Shaping the power relation between states - Rodríguez Barriocanal, Alexandre (Politikon: The IAPSS Journal of Political Science, 2015)
In the 21st century, we are living a new age of international community where different allies are playing a fundamental role in the international equilibrium. The young CSDP in Europe has to mediate and rise in this new scenario where NATO has traditionally been the big defence leader in the European community. In fact CSDP has found different issues over which to provide security to Europe.